Oral Lichenoid lesions induced by programmed cell death protein 1 and cytotoxic T-lymphocyte-associated protein 4 bispecific antibody: a case report - Qiaozhi Jiang; Xinyu Chen; Jiaxuan Wu; Shanni Wei; Renchuan Tao (BMC, 2024)
Abstract Background Cadonilimab is the first approved dual immune checkpoint inhibitor targeting programmed cell death protein 1 (PD-1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), currently utilized for the treatment of various solid tumors. Oral mucosal adverse reactions, such as oral lichenoid lesions, represent one of the most prevalent immune-related adverse events associated with immune checkpoint antibodies. However, reports detailing oral side effects specifically linked to Cadonilimab are lacking. Documenting these side effects is essential to alert oncologists and stomatologists, facilitating timely intervention for affected patients. Case Presentation We present a case involving a 35-year-old male patient diagnosed with hepatocellular carcinoma who received Cadonilimab following hepatectomy and subsequently developed extensive oral lichenoid lesions along with mucosal erosion at 13-14 weeks post-treatment initiation. A biopsy was conducted revealing immunohistochemical findings of CD3+, CD4+, CD8+, CD20 + lymphocytes, CD68 + macrophages, and α-SMA + myofibroblasts infiltrating the tissue of the oral lichenoid lesions. The patient's oral lesions improved after administration of systemic and local glucocorticoid therapy alongside cessation of Cadonilimab treatment. Conclusion This report marks the first documented instance of an oral adverse effect associated with Cadonilimab use. It underscores that administration of this agent may lead to significant lichenoid lesions and erosions within the oral cavity-an issue warranting increased vigilance from both oncologists and stomatologists.